Superradiance of a global monopole in Reissner-Nordstrom(-AdS) space-time - SEÇUK, MUHAMMED HALUK; DELİCE, ÖZGÜR (SPRINGER, 2020)
In this article, the behavior of a charged and massive scalar field around a global monopole swallowed by a Reissner-Nordstrom-Anti-de Sitter (RN-AdS) black hole is investigated by considering the Klein-Gordon equation in this geometry. The superradiance phenomenon and instability behavior of the black hole against charged scalar perturbations are studied for both an RN-AdS case and also for an RN black hole surrounded by a reflective mirror, i.e., the black hole bomb case. The effects of the monopole on these cases are discussed analytically and also with the help of several graphs in detail. The monopole charge affects the superradiance threshold frequency and also effects the instability time scale for both cases. The existence of global monopole makes these black holes more stable against superradiance instability.
Keywords: BLACK-HOLE; GRAVITATIONAL-FIELD; STABILITY; WAVES; AMPLIFICATION; INSTABILITY; EXTRACTION; EVOLUTION; STRINGS; ENERGY